Analisis Perbedaan Pendapatan Usahatani Sawi Semi Organik dan Non Organik di Desa Aunupe Kecamatan Wolasi - Lestari, Fenti Nandia; Rianse, Ilma Sarimustaqiyma; Fyka, Samsul Alam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
Vegetables have various types that can be cultivated, one of which is mustard greens. Sawi is one type of vegetable that is very popular among consumers. Aunupe village is one of the largest mustard producing villages in South Konawe. In cultivating farmers using non-organic farming systems and slowly turning to semi-organic. The aim of the study was to determine the income of mustard farmers using semi-organic and non-organic farming systems and find out how much the income difference between mustard farmers when implementing non-organic farming systems and after implementing semi-organic farming systems in Aunupe Village, Wolasi. District, Konawe Selatan District. The number of mustard farmers as many as 30 farmers. The analysis was carried out using the concept of income and t-test. The results showed that the average income of mustard farming when applying the non-organic farming system was Rp. 231,554/farmer and the income of mustard farming when applying semi-organic farming was Rp. 432,605/farmer. The results of the Paired Sample Test show that there is a difference in income between non-organic mustard farming and semi-organic farming, the income of semi-organic mustard farming is greater than the income of non-organic mustard farming